Framework for Successful Quality Management System in Construction Project - Wan Husni, Wan Nur Eliana (IRC, 2019)
Construction Industry in every country are known as one of the highest contributors to Gross Domestic Sector, which includes Malaysia. With the number of construction project increasing every year in Malaysia, the quality in construction industry have to increase. Based on CIDB reports, it was stated that the quality management in construction industry is not up to standard to compare with other countries.